Comparison of Maternal Serum Levels of Thrombopoietin among Pregnant Women with and without Preeclampsia - Rusul Jabbar Tauma; Zainab H. Al-Kakajy (Kufa Journal for Nursing Sciences)
Background: Preeclampsia is a syndrome and considered one of the most significant causes that can lead to maternal and fetal morbidity and mortality. It is characterized by new onset of hypertension and proteinuria after 20 weeks of gestation. Thrombopoietin is a major regulator of megakaryocyte maturation and platelet production. Thrombopoietin initiates its biologic effects by binding to the myeloproliferative leukemia protein receptor, which is a member of the hematopoietin receptor family.